KEMISKINAN DI DUMA KETIGA DALAM PERSPEKTIF EKONOMIPOLITIKINTERNASIONAL - Setyawan, Anton Agus (Universitas Muhammdaiyah Surakarta, 2001)
Poverty becomes the main problem, which prevents Third World Countries to be equal as any other countries in the world. This issue could be analysing from the development strategies of the Third World countries. They implemented Western Development strategies, which finally failed to overcome the problem. The main cause of the poverty in the Third World countries is the asymmetry in the world political economy. This article discusses this phenomenon by using three different theories: Centre-Periphery theory, Neo-Marxism and Dependency theory and Classic Marxism theory. The conclusion is, the effects of the asymmetry in the world political economy could be minimize by enforcing the global egalitarianism.